mRNA based vaccines as an alternative to conventional vaccine approaches - Zubda-; Muhammad Imran Qadir (Open Journal of Environmental Biology - Peertechz Publications, 2022)
In recent years, vaccines based on mRNA are providing protection against infectious diseases and treatment for cancer. These vaccines offer many advantages as compared to traditional vaccines. They can be rapidly and easily manufactured at a low cost and are reliable for administration. These vaccines can generate both cell-mediated and humoral immunity. Their administration is still limited because of the risk of quick degradation and ineffectiveness after delivery. Technological advancements are recently being made to overcome these issues. This review summarizes current mRNA vaccine development, safety concerns, advances in delivery systems, clinical trials, and various therapeutic applications of mRNA vaccines.